Kriminalisasi dalam Peraturan-peraturan Daerah di Propinsi Daerah Istimewa Yogyakarta dalam Perspektif Politik Kriminal - Muhammad Arif Setiawan (Fakultas Hukum Universitas Islam Indonesia, 2004)
There is any trend of criminal threat in theendorsed laws in Yogyakarta Special province. It especially deals with the regional tax viewed from criminal punishment perspective has been proportioned as the norm of regulation, it seems that to be forced socially and economically. The main aim of enclosing criminal sanction on regulation non-criminal punishment is actually forforcing inorder that society meet the Endorse Laws.